2018
DOI: 10.1080/01913123.2018.1427165
|View full text |Cite
|
Sign up to set email alerts
|

Rat hippocampal CA3 neuronal injury induced by limb ischemia/reperfusion: A possible restorative effect of alpha lipoic acid

Abstract: Limb ischemia reperfusion (I/R) injury is associated with serious local and systemic effects. Reperfusion may augment tissue injury in excess of that produced by ischemia alone. The hippocampus has been reported to be vulnerable to I/R injury. Alpha lipoic acid (ALA) is an endogenous antioxidant with a powerful antioxidative, anti-inflammatory, and antiapoptotic properties. We studied the probable restorative effect of ALA on limb I/R-induced structural damage of rat hippocampus. Forty adult male albino rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Conjugated linoleic acid has been shown to alter the levels of TNF-α, IL-1β, and RANTES in cultured human astrocytes [192]. Within the context of ischemia, intravenous injection of α-lipoic acid reduced neuronal damage in a rat model of ischemia but did not reduce astrogliosis [193].…”
Section: Astrocyte Lipid Signalling and Inflammation In Diseasementioning
confidence: 99%
“…Conjugated linoleic acid has been shown to alter the levels of TNF-α, IL-1β, and RANTES in cultured human astrocytes [192]. Within the context of ischemia, intravenous injection of α-lipoic acid reduced neuronal damage in a rat model of ischemia but did not reduce astrogliosis [193].…”
Section: Astrocyte Lipid Signalling and Inflammation In Diseasementioning
confidence: 99%
“…LA treatment also attenuated the injuries of other tissues caused by limb I/R. A recent study [ 100 ] showed that limb I/R induced the degenerative injury of rat hippocampal CA3 neurons (e.g., the reduction of light neuron number, surface areas of neurons, and the thickness of the CA3 layer together with increased capillary lesions), and an injection of LA (100 mg/kg, i.p) for 7 d significantly ameliorated these damages. The result indicated the potential application of LA in both nervous system and peripheral tissues simultaneously induced by limb I/R.…”
Section: The Effects Of La On I/r Injuries Of Different Organsmentioning
confidence: 95%
“…Limb ischemia reperfusion injury (LIRI) is a combination of limb ischemia injury and reperfusion injury, which is a common and complicated pathological process after severe clinical trauma with high morbidity and mortality. 1 Replantation of severed limb, crush injury, thrombosis of lower extremities, repair of abdominal aortic aneurysm, and traumatic arterial injury are the main causes of LIRI which can not only damage the local tissues of the limbs, but also affect the distal viscera. 2 The pathological mechanisms of limb ischemia-reperfusion injury are considered to include oxygen free radicals, lipid peroxidation, excitatory neurotransmitter effect, calcium overload, and inflammatory damage.…”
Section: Introductionmentioning
confidence: 99%